Sexual Function in Men Living With a Fontan Circulation - Rubenis, Imants; Tran, Derek; Bullock, Andrew; Wijesekera, Vishva; Baker, David; d'Udekem, Yves; du Plessis, Karin; Katz, Darren; Lowy, Michael; Zentner, Dominica; Celermajer, David; Cordina, Rachael (Frontiers in Pediatrics, 2021)
Introduction: It is unknown if the Fontan circulation has an impact on sexual health in men. This study assessed self-reported sexual health and fertility in men with a Fontan circulation. Aims: In this prospective, cross-sectional study, Australian men ≥18 years enrolled in the Fontan Registry of Australia and New Zealand were invited to complete the International Index of Erectile Function (IIEF), alongside questions assessing fertility. These data were compared to historical, age-matched controls. Results: Of 227 eligible men, 54 completed the survey; of those 37 were sexually active and included in the final analysis. Mean age was 28±3 years, age at Fontan was 5±3 years. Fontan type was extra-cardiac conduit in 15(41%), lateral tunnel in 12 (32%), and atriopulmonary connection in 10 (27%). Ventricular function was normal in 24 (83%), and all were New York Heart Association Class I (23 patients,79%) and II (six patients, (21%). Nine participants (24%) had erectile dysfunction (IIEF-EF score ≤25). The severity was mild (IIEF 22 – 24) in six (16%), mild – moderate (IIEF 17 – 21) in two (5%), and moderate (IIEF 11 – 16) in one (3%). Baseline characteristics and current medication usage were similar in those with and without erectile dysfunction. Compared with historical control values, erectile function was not significantly impaired in the Fontan population (p=0.76). Men with a Fontan circulation had decreased levels of sexual desire and overall satisfaction (p < 0.001). There was no correlation between the presence of erectile dysfunction and any assessed parameter. Eleven (30%) of the cohort reported a pregnancy with a prior partner. Conclusion: In our cohort, overall erectile function was comparable between men with a Fontan circulation and historical controls, however sexual desire and overall satisfaction were reduced. There was no correlation between study parameters and the presence of erectile dysfunction. The proportion of the cohort who had a prior pregnancy was congruent with population data.